Xpress Bowl - Chang, Nikki (Nanyang Technological University, 2020)
The Xpress Bowl aims to provide a good alternative for disposable takeaway meal packaging in bid to reduce Singapore's plastic consumption and hence extend the lifespan of the Pulau Semakau Landfill. By tackling the main drawbacks of current lunchboxes found by survey and research, the Xpress Bowl encourages a lifestyle switch to using reusable lunchboxes for takeaway meals by meeting the needs of busy Singaporeans. Through many rounds of trial and error, the Xpress Bowl is a designed with a form that is collapsible yet secured by a button buckle. It also has an inner thin, flexible silicone lining that stores the food and is replaceable if needed, extending the product's lifespan. It is made of sustainable or recycled materials as well, not adding on to the waste problem. The Xpress Bowl is specially catered for tertiary-level education students and working adults, as it is collapsible for efficient storage and the silicone lining can be flipped inside out for easy cleaning. It can also be carried using its handles and is even equipped with a utensil set for maximum convenience. These functionalities are all packed in one sleek and modern design - The Xpress Bowl.